2022
DOI: 10.3390/jcdd9120428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thymoquinone Alone or in Combination with Losartan on the Cardiotoxicity Caused by Oxidative Stress and Inflammation in Hypercholesterolemia

Abstract: Dietary cholesterol accelerates oxidative and pro-inflammatory processes, causing hypercholesterolemia and cardiovascular diseases. Thus, the purpose of the current study is to compare the protective effects of thymoquinone (TQ) alone or in combination with losartan (LT) against the heart damage caused by a high-cholesterol diet (HCD). HCD-fed rat groups revealed an elevated activity of indicators of cardiac enzymes in the serum. Serum and cardiac lipids were also found to be significantly higher in HCD-fed ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Vitamin D deficiency is assumed to be one of the early stages of metabolic disorders having an impact on CVD. In particular, hypertension due to renin-angiotensin system disorder, hyperlipidemia, especially increased low-density lipoproteins (LDL), hyperglycemia in diabetic patients and increased inflammation and oxidative stress biomarkers are some of the mechanisms probably connecting vitamin D deficiency and CVD [17]. Haybar et al concluded that vitamin insufficiency is related to decreased coronary flow, which impairs endothelial function and promotes atherosclerosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency is assumed to be one of the early stages of metabolic disorders having an impact on CVD. In particular, hypertension due to renin-angiotensin system disorder, hyperlipidemia, especially increased low-density lipoproteins (LDL), hyperglycemia in diabetic patients and increased inflammation and oxidative stress biomarkers are some of the mechanisms probably connecting vitamin D deficiency and CVD [17]. Haybar et al concluded that vitamin insufficiency is related to decreased coronary flow, which impairs endothelial function and promotes atherosclerosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…2 Inflammatory alterations, osteogenesis, angiogenesis, and endothelial dysfunction are among the crucial factors associated with the pathogenesis of atherosclerosis, all of which are either directly or indirectly influenced by vitamin D. 3 Numerous studies have investigated the correlation between vitamin D status and various aspects of cardiovascular disorders, such as metabolic syndrome, hypertension, or fatal events associated with coronary artery disease (CAD). 4,5 In light of these findings, there is a growing call for heightened attention to the potential role of vitamin D deficiency as a risk factor for CAD. Nevertheless, the existing evidence remains inconclusive due to conflicting reports in the literature, with some supporting and others opposing this concept.…”
Section: Introductionmentioning
confidence: 99%